METODE PELAKSANAAN PERKERASAN LENTUR (FLEXIBEL PAVEMENT) PADA TANAH DASAR LUNAK - Hasriana, Hasriana (FORUM BANGUNAN, 2013)
The goal to be achieved in the preparation of this thesis is to find out the solutions used to overcome problems caused by soft subgrade on a flexible pavement construction (flexible pavement). In addition to known advantages and disadvantages of each of the solutions to deal with the problems posed by soft soils in a flexible pavement construction.